Improving reference management skills through mendeley training and APA style citation techniques and submitting articles to OJS-based journals - Herinda Mardin; La Nane (Fisheries and Society Publisher, 2021)
This Mendeley training aims to provide skills to participants regarding reference management and APA style citation techniques using Mendeley software, as well as how to submit articles in OJS-based journals. The method used in this training is Participant Active Learning which is followed by 42 participants. Some of the things that resulted from this training activity were 1) Participants were very enthusiastic about listening to the presentation of material related to an overview of Mendeley, how to do reference management using Mendeley software; 2) Participants were very enthusiastic in participating in the explanation of material related to APA style citation techniques using Mendeley software; 3) Participants actively participate in technical guidance and hands-on practice on how to perform reference management and APA style citation techniques using Mendeley; 4) Participants enthusiastically listen to the presentation of the material and the simulation submits articles to OJS-based journals. The conclusion of this training activity is that the activity went very well and smoothly even though there was a slight problem with the internet network, but it could still be overcome. The results obtained by the participants after participating in this training activity are: 1) Participants have skills in applying Mendeley as a tool for reference management; 2) Participants have the skills to do APA style citations using Mendeley software; 3) Participants have knowledge and insight about the mechanism for submitting articles in OJS-based journals.